Biliary fasciolosis differential diagnosis of choledocholithiasis. Caso report and literature review - Vera-Portilla, Angel F. (2024)
Peru is one of the countries with the greatest regional distribution of human fascioliasis caused by F. hepatica in the world, it was considered an emerging disease and can have high morbidity. We present the case of a 41-year-old woman who presented with abdominal pain. Ultrasound showed cholelithiasis and choledocholithiasis; and the cholangioresonance study showed bile duct dilation and distal stenosis. A retrograde endoscopic cholangiopancreatography was made and we removed two parasites similar to hepatic flukes. Subsequently, the cholecystectomy could not be performed due to delay and request for voluntary discharge. In our environment, even today, there is a need to suspect fascioliasis, in the case of a compatible clinical of choledocholithiasis in patients from endemic regions. Therefore, knowing the best study alternatives and appropriate treatment according to the phase of the disease is important to effectively combat this disease.